EMPOWERING CHILDREN THROUGH CIRCLE TIME: AN INTERVENTION TO PROMOTE LANGUAGE INTERACTION IN PRIMARY ESL CLASSROOM IN MALAYSIA (Practitioner Research, 2019)
As Malaysian English curriculum changes in accordance to the needs and demands of education all across the world, so must the teaching of English as the second language (L2) in Malaysian schools. Every year there are many approaches and innovations introduced to the community of educators to cater to these changes and amongst many is the use of Circle Time. This paper investigates the use of Circle Time in supporting ESL pupils’ language interactions in classroom by looking at the types and frequencies of language interactions that occur during lessons. This is to determine if Circle Time is indeed beneficial in supporting second language interaction in the classroom. Classroom observations were conducted on two classes of Year Three which utilized Circle Time. Besides the frequency, the kind of interactions that occurred during Circle Time were also observed using an observation checklist. Lastly, two English teachers were interviewed to find out their perspectives on the implementation. Findings of this study showed that there were trends in the frequency of seven of the types of language interaction that occurred during Circle Time. Besides, the interviewed teachers identified two advantages of Circle Time on their pupils’ interactions and to sum up, Circle Time is a suitable intervention strategy to promote language interactions of English as a Second Language among Malaysian primary schools.